IMPROVING 4th GRADE STUDENTS’ LEARNING COMPETENCY THROUGH STUDENT TEAMS ACHIEVEMENT DIVISIONS METHOD - Dwi Aryani; Slameto Slameto (Universitas Pendidikan Ganesha, 2017)
This study aims to improve science learning outcomes through methods of Student Teams Achievement Divisions. Action Research (PTK) is conducted in two cycles. The research procedures based on the Kemmis and Mc Tanggart models include planning, action, observation and reflection phases that are adapted to the Student Teams Achievement Divisions.The results obtained from the implementation of cycle I and II, namely an increase learning outcomes after using Student Teams Achievement Divisions. In comparison the initial conditions, the cycle I and II show the initial conditions only 9 students, or 36%, in the first cycle of 16 students or 64% and the second cycle increased to 23 students or 92%. Based on the results concluded that Student Teams Achievement Divisions learning to improve student learning outcomes with indicators of >70%, which indicates success.